Study on the Floating of Large Diameter Underwater Shield Tunnel Caused by Synchronous Grouting. (23rd June 2022) - Liang, Yu; Huang, Xumin; Gao, Shijun; Yin, Yihao
Abstract : Synchronous grouting is the key factor causing segment floating during the construction of shield tunnel, especially the grout ratio and the control of the grouting pressure. In this paper, the ratio of grout material was optimized through multiple groups of physical and mechanical tests. The results showed that 0.3% content of water reducing agent in grout could improve the ability of water resistance significantly. 2.9% content of bentonite could reduce bleeding rate of grout and grout setting time and improve the fluidity in the meantime. Then, the distribution law of grout along the segment ring in the filling stage was studied based on a typical underwater tunnel in China. The results showed that the theoretical calculation of grouting pressure was between 0.15 MPa and 0.18 MPa, which were in good agreement with the measured data. The grouting pressure distribution is affected by four parts including the lateral earth pressure, foundation reaction, grout shear stress, and gravity.